ANALISA USAHA PETERNAKAN KAMBING PERANAKAN ETAWA (PE) (Studi Kasus di Kelompok Ternak Berkah Etawa) - Rofiq Ghozali (Universitas Islam Balitar, 2016)
The research was conducted at the Livestock Group -˜Berkah Etawa ’ Domot Hamlet, Purwokerto Rural , District Srengat , Blitar . The study was conducted in the span of one month , which began on 2 March to 2 April 2013. The purpose of this study was to determine the analysis of goat farms in the herd and when it happens Blessing Etawa BEP ( Break Even Point) .The material in this study is a goat farmer group members by using descriptive qualitative method in the form of case studies . Methods of data collection by surveys , interviews with the questions and observation ( observation ) . Then the data were analyzed with descriptive analysis method . By maintaining 145 or 16 ST tail , in 1 year will cost Rp . 136 742 500 , -/year . revenues generated by Rp . 228.7 million . If the selling price of milk Rp . 20,000 , -/liter the breakeven point ( BEP ) production of 621.57 liters / year per member . While the break-even point ( BEP ) prices , if we sell at a price of Rp . 18288.51 / liter .Keywords : Goat Farm, BEP (Break Event Point).